The new generation tyrosine kinase inhibitor improves the survival of chronic myeloid leukemia patients after allogeneic stem cell transplantation. Issue 3 (12th April 2022) - Shimazu, Yutaka; Murata, Makoto; Kondo, Takeshi; Minami, Yosuke; Tachibana, Takayoshi; Doki, Noriko; Uchida, Naoyuki; Ozawa, Yukiyasu; Yano, Shingo; Fukuda, Takahiro; Kato, Jun; Ara, Takahide; et al.
Abstract: The introduction of tyrosine kinase inhibitors (TKIs) in chronic myeloid leukemia (CML) treatment has dramatically improved the prognosis of CML patients and reduced the number of patients receiving allogeneic stem cell transplantation (allo‐SCT). However, the impact of the newest‐generation TKIs on the overall survival (OS) after allo‐SCT has not been well described. To investigate the beneficial effects of TKIs on the prognosis after allo‐SCT, we conducted a retrospective observational study using the Transplant Registry Unified Management Program database in Japan. We analyzed 1188 patients (male/female: 738/450; median age: 44 years; range: 16–75) who underwent their first allo‐SCT between January 2001 and December 2018. We divided the patients into two groups according to the TKI treatment used before allo‐SCT: group 1 was treated with the first generation TKI imatinib; group 2 was treated with the second generation TKIs nilotinib, dasatinib, or bosutinib and/or the third generation TKI ponatinib. We compared the post allo‐SCT OS between the two groups. The 3‐year OS rates (95%CI) of groups 1 and 2 were 59.3% (54.8%–63.5%) and 65.8% (61.6%–69.6%), respectively ( p = 0.017). Multivariate analysis confirmed that group 2 had superior OS after allo‐SCT compared to group 1 ( p = 0.002). Other factors associated with superior prognosis were age ≤65, performance status (PS) 0/1, a 6/6 HLA‐matched donor and chronic‐phase (CP) disease status at allo‐SCT. A subgroup analysis showed poor prognoses for patients who could not obtain a molecular response before allo‐SCT and patients with positive T315I mutation in the BCR/ABL gene. In group 2, early allo‐SCT was correlated with superior OS in patients with a blast‐crisis disease status at allo‐SCT ( p = 0.001). The cumulative incidence of non‐relapse mortality rate significantly decreased in group 2 ( p = 0.0005). The post allo‐SCT OS was improved both by pre‐ and post‐management of allo‐SCT and by the introduction of newer TKIs.